TEKNIK PERMAINAN BIOLA PADA LAGU PIE JESU KARYA ANDREW LLYOD WEBBER - Eno Seylin Yosepin; Christanto Hadijaya; Martha Malau (STT Kristus Alfa Omega, 2023)
The results of research conducted by researchers on the analysis of the technique of playing violin song Pie Jesu by Andrew Llyod Webber. Violin playing techniques that generally implement violin playing techniques in general by understanding the original score in the vocal version of the song which is interpreted into violin playing techniques, this make it easier to analyze violin playing techniques including bowing, expression, dynamics, and articulation. A deep interpretation is needed in converting vocal music into instrumental music so that the meaning contained in the song is still conveyed.